Proceedings of the 2nd Workshop on Many-Task Computing on Grids and Supercomputers 2009
DOI: 10.1145/1646468.1646469
|View full text |Cite
|
Sign up to set email alerts
|

Robust workflows for science and engineering

Abstract: Scientific workflow tools allow users to specify complex computational experiments and provide a good framework for robust science and engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In one case study, we used the NIMROD/G tool to perform an example of this, and in a second, we showed that the more selective and efficient search functions in NIMROD/O allow us to compute parameter values that optimize some objective function. Although we did not demonstrate the third member of the NIMROD family, NIMROD/E, it has also been applied to solving complex problems in cardiac models in the past (Abramson et al 2009). …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In one case study, we used the NIMROD/G tool to perform an example of this, and in a second, we showed that the more selective and efficient search functions in NIMROD/O allow us to compute parameter values that optimize some objective function. Although we did not demonstrate the third member of the NIMROD family, NIMROD/E, it has also been applied to solving complex problems in cardiac models in the past (Abramson et al 2009). …”
Section: Discussionmentioning
confidence: 74%
“…Currently, we are building a new version of NIMROD, NIMROD/K, that better supports running sweeps over workflows in which multiple tools are connected to solve a single modelling problem (Abramson et al , 2009. NIMROD/K leverages KEPLER (Altintas et al 2005), a multi-institution collaboration, to build a scientific workflow system for the grid.…”
Section: Discussionmentioning
confidence: 99%
“…The average (mean) bytes per write call were 7,976 bytes, with a standard deviation of 1,584 bytes. The median bytes per call were again 2 pages (8,192 bytes)…”
Section: I/o Needs Of the Ocean Modelmentioning
confidence: 99%
“…Section 3 describes ESSE [5], [6], the data assimilation and error estimation approach used. Section 4 describes the ESSE implementation as a MTC application ( [7], [8], [9]) and the options we face in terms of optimizing I/O issues. This is followed in Section 5 by a discussion of the practical MTC use of ESSE on local clusters, Grids and Amazon EC2.…”
Section: Introductionmentioning
confidence: 99%
“…Kepler pursues another approach which consists in wrapping the resources of other SWMSs, e.g., the Nimrod engine to improve its parameter sweeping support (Abramson et al 2009 ) . Recent developments in the fi eld and the adoption of service-oriented architecture standards by most systems should allow for interoperability.…”
Section: Execution Supportmentioning
confidence: 99%